T2 mapping MRI technique quantifies carotid plaque lipid, and its depletion after statin initiation, following acute myocardial infarction. (December 2018) - Alkhalil, Mohammad; Biasiolli, Luca; Akbar, Naveed; Galassi, Francesca; Chai, Joshua T.; Robson, Matthew D.; Choudhury, Robin P.
Abstract: Background & aims: A recently-validated, highly-sensitive T2 mapping magnetic resonance (MRI) technique accurately quantifies carotid plaque lipid. The aims of this study were to determine: (i) the extent of carotid plaque lipid in patients with acute coronary syndromes (ACS); (ii) the effects of initiation of high-intensity statin on plaque lipid content and (iii) whether plaque lipid content is related to standard or 'functional' blood lipid measurements. Methods: Statin naïve subjects presenting with ACS underwent carotid artery MRI at 3 T scanner to quantify plaque lipid. Patients were subsequently commenced on high dose statin as part of clinical care and underwent a second MRI after three months. Plaque composition was measured using objective semi-automated techniques. Results: 23 out of 24 patients had measurable lipid. Three months after statin initiation there was a significant reduction in carotid lipid percentage [from 10.3% (7.2–14.2) to 7.4% (5.4–10.0), p  = 0.002] and a significant increase in fibrous percentage [from 83.3% ± 6.6–85.5% ± 4.8, p  = 0.039]. None of the studied functional blood biomarkers were related to either baseline carotid plaque lipid content or its propensity to change with statin treatment. Conclusions: T2-mapping demonstrated depleted carotid plaque lipid following the initiation of high-intensity statin treatment. Standard or 'functional' blood biomarkers were dissociated from plaque lipid content or changes with treatment. These findings further reinforce the importance of disease characterisation over risk factor assessment. Subject to clinical trial findings, quantification of plaque lipid may provide the basis for an approach to identify patients suitable for intensive lipid reduction regimes. Highlights: T2 mapping is a newly-validated magnetic resonance (MRI) technique that can quantify carotid lipid content in patients who were not pre-screened for carotid atherosclerosis. T2 mapping can detect reduction in carotid lipid content following three months of statin treatment. This reduction in plaque lipid was not related to blood lipid measurements suggesting that these measurements are not substitutes for quantifying plaque lipid. These findings support the use of plaque imaging to identify patients who may be suitable for intensive lipid treatments.